2021
DOI: 10.1371/journal.pone.0251911
|View full text |Cite
|
Sign up to set email alerts
|

Constitutive activation of CTNNB1 results in a loss of spermatogonial stem cell activity in mice

Abstract: Spermatogenesis requires that a careful balance be maintained between the self-renewal of spermatogonial stem cells (SSCs) and their commitment to the developmental pathway through which they will differentiate into spermatozoa. Recently, a series of studies employing various in vivo and in vitro models have suggested a role of the wingless-related MMTV integration site gene family/beta-catenin (WNT/CTNNB1) pathway in determining the fate of SSCs. However, conflicting data have suggested that CTNNB1 signaling … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(10 citation statements)
references
References 61 publications
2
8
0
Order By: Relevance
“…Among these, 23 mitosisrelated proteins were used to establish the PPI network by using Cytoscape and three genes in the PPI network were identified as hub genes, including CTNNB1, CUL4B, and RUVBL1. For instance, a recent study revealed that CTNNB1 is an essential regulator of murine spermatogonial stem cell fate to induce its differentiation into spermatogonia (35). In this study, we found that decreases in mRNA and protein levels of CTNNB1 with increasing age, suggestive of its importance for the early stages of Tibetan sheep spermatogenesis.…”
Section: Discussionsupporting
confidence: 58%
“…Among these, 23 mitosisrelated proteins were used to establish the PPI network by using Cytoscape and three genes in the PPI network were identified as hub genes, including CTNNB1, CUL4B, and RUVBL1. For instance, a recent study revealed that CTNNB1 is an essential regulator of murine spermatogonial stem cell fate to induce its differentiation into spermatogonia (35). In this study, we found that decreases in mRNA and protein levels of CTNNB1 with increasing age, suggestive of its importance for the early stages of Tibetan sheep spermatogenesis.…”
Section: Discussionsupporting
confidence: 58%
“…A subsequent study using a Ctnnb1 tm1Mmt/tm1Mmt ; Ddx4 cre/+ model showed that the constitutive activation of β-catenin in fetal gonocytes triggered SSC proliferation and spermatocyte depletion 53 . However, using the Ctnnb1 tm1Mmt/tm1Mmt ; Ddx4 cre/+ model, Boyer et al ., found that the constitutive activation of β-catenin in fetal gonocytes compromised SSCs activity and promoted SSCs differentiation 54 . In addition, the constitutive activation of β-catenin in fetal gonocytes using a Ctnnb1 tm1Mmt/tm1Mmt ; Nanos3 cre/+ model reduced the GFRα1 + SSC pool 55 .…”
Section: Discussionmentioning
confidence: 99%
“…Catenin beta-1; WNT binds CTNNB1 pathway mediates proliferation of progenitor cells and spermatogonial stem cells in spermatogenesis process. [11] Lgals3 Galectin-3; Galactose-specific lectin which binds IgE. May mediate with alpha-3, beta-1 integrin the stimulation by CSPG4 of endothelial cell migration.…”
Section: Ctnnb1mentioning
confidence: 99%
“…Vimentin is an intermediate filament that extends from the nuclear periphery to the cell membrane, and is connected with the tubulin and actin cytoskeleton [10]. The cellular functions of vimentin contribute to cellular stiffness, actin position, cell migration, cell division, and organelle organization in different stages of spermatogenesis [10,11]. In addition, vimentin plays other vital roles, such as determining cell shape, cell differentiation, cell motility, maintaining cell junctions, assisting in keeping ordinary spermatogonia morphology, and playing a main role in anchoring differentiating germ cells to the seminiferous epithelium [12,13].…”
Section: Introductionmentioning
confidence: 99%